2005
DOI: 10.1182/blood-2004-10-3900
|View full text |Cite
|
Sign up to set email alerts
|

HOXA genes are included in genetic and biologic networks defining human acute T-cell leukemia (T-ALL)

Abstract: Using a combination of molecular cytogenetic and large-scale expression analysis in human T-cell acute lymphoblastic leukemias (T-ALLs), we identified and characterized a new recurrent chromosomal translocation, targeting the major homeobox gene cluster HOXA and the TCRB locus. Real-time quantitative polymerase chain reaction (RQ-PCR) analysis showed that the expression of the whole HOXA gene cluster was dramatically dysregulated in the HOXA-rearranged cases, and also in MLL and CALM-AF10 -related T-ALL cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
428
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(450 citation statements)
references
References 77 publications
18
428
0
4
Order By: Relevance
“…cDNA microarray studies have revealed that overexpression of late Hoxa genes and Bmi-1 are a characteristic of leukaemias involving CALM-AF10 and some MLL-fusion proteins [12][13][14] . In particular, over-expression of Hoxa9 has been demonstrated to be crucial for leukaemias involving MLL-ENL and MLL-AF10 fusion proteins 5,15,16 .…”
mentioning
confidence: 99%
“…cDNA microarray studies have revealed that overexpression of late Hoxa genes and Bmi-1 are a characteristic of leukaemias involving CALM-AF10 and some MLL-fusion proteins [12][13][14] . In particular, over-expression of Hoxa9 has been demonstrated to be crucial for leukaemias involving MLL-ENL and MLL-AF10 fusion proteins 5,15,16 .…”
mentioning
confidence: 99%
“…Gene expression analysis showed that the whole HOXA gene cluster was dramatically dysregulated in T-cell acute lymphocytic leukemia samples harboring the TCRb-HOXA rearrangement (Speleman et al, 2005;Cauwelier et al, 2007). HOXA genes were also found to be upregulated in MLL and CALM-AF10-related T-cell acute lymphoblastic leukemias cases, strongly suggesting that HOXA genes are oncogenic in these leukemias (Soulier et al, 2005).…”
Section: Deficiencies Of Hox Regulators Demonstrate a Role For Hox Gementioning
confidence: 99%
“…59 Chromosomal translocations also lead to ectopic expression of HOXA cluster genes by juxtaposition of TCRA regulatory elements with HOXA coding sequences in some patients with T-cell ALL. 60,61 In addition to these translocations, which directly lead to overexpression of HOX genes, a number of recent studies have demonstrated that chromosome translocations, which result in MLL fusions, lead to unscheduled expression of HOX genes in both AML and T-cell ALL patients. 62 In addition to these studies showing HOX gene dysregulation resulting from chromosomal translocations, global gene Role of CALM-AF10 gene fusion in acute leukemia D Caudell and PD Aplan expression profiling has identified HOX genes as being consistently overexpressed in AML.…”
Section: Role Of Calm-af10 Gene Fusion In Acute Leukemia D Caudell Anmentioning
confidence: 99%